The Impact of Sex and Performance Level on Pacing Behavior in a 24-h Ultramarathon - Inoue, Allan; Santos, Tony Meireles; Hettinga, Florentina J.; Alves, Daniel de Souza; Viana, Bruno Ferreira; Terra, Bruno de Souza; Pires, Flávio Oliveira (Frontiers in Sports and Active Living, 2019)
Purpose: We analyzed the impact of sex, performance level and substantial speed reductions (SSR) on pacing in the Rio 24-h Marines Ultramarathon. This will provide insights into the importance of minimizing variations in speed in relation to optimal pacing in endurance events. Methods: Runners (30 males and 21 females), classified as high- (HP) and low-performance (LP) ran the race while having their time recorded every 400 m. The pacing was analyzed as the first 10% (initial epoch), the following 80% (intermediate epoch) and the last 10% of the race (final epoch). The time percentage spent at speeds < 3.5 km∙h-1 (SSR), 3.5 to 5.9 km∙h-1 (walking speed), 6.0 to 8.0 km∙h-1 (walk-to-running transition speed) and > 8.0 km∙h-1 (running speed) was calculated. Results: Runners showed a reverse J-shaped pacing (P<0.001) regardless of sex and performance level, although male (P<0.004) and HP runners (P<0.001) have preserved a higher mean speed throughout the race. Male and HP runners spent more time at running speed (P < 0.001) and less time at SSR (P<0.001) than female and LP runners. Total distance was inversely correlated with the number of SSR and speed CV in male (r= -0.47 and r= -0.64, respectively) and female (r= -0.61 and r= -0.47, respectively). Conclusion: Male, HP runners showed less SSR, conserving a higher mean speed with less variation throughout the race. Results suggest that conservative pacing strategies, with lower speeds in the beginning and higher speeds towards the end, may be the most adequate for different endurance running disciplines. Results also show different competition dynamics between men and women, which warrants further exploration in ultramarathons as well as other IAAF events.